Adult Ileo-Ileo-Caecal Intussusception: Case Report and Literature Review. (17th December 2012) - Singhal, Sanjeev; Singhal, Anu; Arora, Pankaj K.; Tugnait, Rahul; Tiwari, Bishwanath; Malik, Pawan; Dhuria, Ankur Subhash; Varghese, Vineet; Bharali, Mriganka Deuri; Chandrakant, Singh; Pushkar,; Panwar, Vishnu; et al.
Abstract : Adult intussusception is a rare entity accounting for only 5% of all intussusceptions and causes approximately 1% of all adult intestinal obstructions. Unlike paediatric intussusceptions which are usually idiopathic, there is usually a lead point pathology which might be malignant in up to 50% cases. We present an unusual case of adult intussusception which was not diagnosed on any investigation including computerized tomographic (CT) scan and magnetic resonance imaging (MRI). It was a case of ileo-ileo-cecal intussusception caused by a large lipoma 38 mm × 43 mm × 61 mm . It was treated by emergency laparotomy for acute intestinal obstruction. A conservative resection with ileostomy was performed with good postoperative recovery.